The Role of PI3K Inhibition in the Treatment of Breast Cancer, Alone or Combined With Immune Checkpoint Inhibitors - Zhang, Zhizhu; Richmond, Ann (Frontiers in Molecular Biosciences, 2021)
Dysregulation of phosphoinositide 3-kinase (PI3K) signaling is highly implicated in tumorigenesis, disease progression, and the development of resistance to the current standard of care treatments in breast cancer patients. This review discusses the role of PI3K pathway in breast cancer and evaluates the clinical development of PI3K inhibitors in both early and metastatic breast cancer settings. Further, this review examines the evidence for the potential synergistic benefit for the combination treatment of PI3K inhibition and immunotherapy in breast cancer treatment.